Integrating Environmental Education for Sustainability - Joel Jonathan Kayombo; Syed Nitas Iftekhar; Leatitia Gabriel Mashaza (Nordic Journal of Comparative and International Education)
This study employs a qualitative inquiry and a phenomenological case study design to critically examine environmental pedagogies within the context of Tanzanian secondary schools. The primary aim is to identify the contextual needs for reorienting education towards environmental justice through the lens of ecopedagogy. Specifically, the research explores three key aspects: stakeholders’ perceptions of the human-environment relationship, the integration of environmental education into school curricula, and stakeholders' recommendations for enhancing environmental education in secondary schools. Guided by the Ecopedagogical Pyramid Framework, the study informs both data collection and the interpretation of findings. The study highlights the importance of environmental education in Tanzania, highlighting the need for a multidisciplinary approach to teach students about environmental issues. It calls for a balance between theory and practice, focusing on practical, action-oriented approaches. The Ecopedagogical Pyramid Framework, which advocates for a balance between theory and practice, can help foster environmental competencies in secondary school students. The study also emphasizes the role of media in shaping environmental consciousness but also calls for more government resources and teacher training to ensure effective environmental education.